12
$\begingroup$

In an example I had to prove that $\sin^2(x)+\cos^2(x)=1$ which is fairly easy using the unit circle. My teacher then asked me to show the same thing using the following power series:$$\sin(x)=\sum_{k=0}^\infty\frac{(-1)^kx^{2k+1}}{(2k+1)!}$$ and $$\cos(x)=\sum_{k=0}^\infty\frac{(-1)^kx^{2k}}{(2k)!}$$ However, if I now take the squares of these values I get a really messy result that I can't simplify to 1.

Could anyone give me a hint on how to deal with this question?

$\endgroup$
3
  • $\begingroup$ Have you tried just trying to find the power series manually (like find the first term, then the second and so on) and see if you can construct a power series)? $\endgroup$
    – InsigMath
    Mar 26, 2014 at 21:59
  • $\begingroup$ Good idea, I have only focussed on the power series given in the example. Will try to construct a joint power series tomorrow. $\endgroup$ Mar 26, 2014 at 22:02
  • 1
    $\begingroup$ Hint: Differentiate the power series. We get that (surprise) the derivative of sine is cos, and the derivative of cos is $\dots$. Let $f(x)=\sin^2 x+\cos^2 x$. Show its derivative is $0$. $\endgroup$ Mar 26, 2014 at 22:05

6 Answers 6

11
$\begingroup$

Hint: Differentiate $\cos^2x+\sin^2x$, and notice that it is $2\cos x\cos'x+2\sin x\sin'x$. Evaluate the expressions of $\sin'x$ and $\cos'x$, and notice that they are the same as those of $\cos x$ and $-\sin x$ respectively. Then you get $\big(\cos^2x+\sin^2x\big)'=0\iff\cos^2x+\sin^2x=$ constant. How do we guess which constant exactly ? By computing $\sin^20+\cos^20$.

$\endgroup$
8
$\begingroup$

Hint: Differentiate the power series term by term. We get that (surprise!) the derivative of $\sin x$ is $\cos x$, and the derivative of $\cos x$ is $-\sin x$. Let $f(x)=\sin^2 x+\cos^2 x$. Show its derivative is $0$. Thus $f(x)$ is constant.

$\endgroup$
6
$\begingroup$

It is not necessary to use derivatives. It is much simpler if we connect the series for $\sin x$ and $\cos x$ with the series of $\exp(x)$. From the given series it is easy to show that $\cos x + i\sin x = \exp(ix)$ and $\cos x - i\sin x = \exp(-ix)$ where $$\exp(z) = \sum_{n = 0}^{\infty}\frac{z^{n}}{n!}$$ and using binomial theorem it is easy to show that series of $\exp(z)$ satisfies $$\exp(z + z') = \exp(z)\cdot \exp(z')$$ and therefore $$\begin{aligned}\cos^{2}x + \sin^{2}x &= (\cos x + i\sin x)(\cos x - i\sin x)\\&= \exp(ix)\exp(-ix)\\&= \exp(0)\\&=1\end{aligned}$$

$\endgroup$
6
$\begingroup$

You can also prove this identity directly from the power series $$ \begin{align} \cos x &= \sum_{n = 0}^\infty \frac{(-1)^n}{(2n)!} x^{2n},\\ \sin x &= \sum_{n = 0}^\infty \frac{(-1)^n}{(2n + 1)!} x^{2n + 1}. \end{align} $$

The following is modified from the discussion on Wikipedia's article on the Pythagorean Trigonometric Identity.

Squaring each of these series using the Cauchy Product $$\left(\sum_{i=0}^\infty a_i x^i\right) \cdot \left(\sum_{j=0}^\infty b_j x^j\right) = \sum_{k=0}^\infty \left(\sum_{l=0}^k a_l b_{k-l}\right) x^k\,,$$ and combining the factorials into a binomial coefficient we get $$\begin{align} \cos^2 x & = \sum_{i = 0}^\infty \sum_{j = 0}^\infty \frac{(-1)^i}{(2i)!} \frac{(-1)^j}{(2j)!} x^{(2i) + (2j)} \\ & = \sum_{n = 0}^\infty \left(\sum_{i = 0}^n \frac{(-1)^n}{(2i)!(2(n - i))!}\right) x^{2n} \\ & = 1 + \sum_{n = 1}^\infty \left( \sum_{i = 0}^n {2n \choose 2i} \right) \frac{(-1)^n}{(2n)!} x^{2n}\,,\\ \sin^2 x & = \sum_{i = 0}^\infty \sum_{j = 0}^\infty \frac{(-1)^i}{(2i + 1)!} \frac{(-1)^j}{(2j + 1)!} x^{(2i + 1) + (2j + 1)} \\ & = \sum_{n = 1}^\infty \left(\sum_{i = 0}^{n - 1} \frac{(-1)^{n - 1}}{(2i + 1)!(2(n - i - 1) + 1)!}\right) x^{2n} \\ & = \sum_{n = 1}^\infty \left( \sum_{i = 0}^{n - 1} {2n \choose 2i + 1} \right) \frac{(-1)^{n - 1}}{(2n)!} x^{2n}. \end{align} $$

Adding the squared series we can combine the odd and even terms then use the binomial theorem to simplify the internal sum to zero: $$ \begin{align} \cos^2 x + \sin^2 x & = 1 + \sum_{n = 1}^\infty \left(\sum_{i = 0}^{n}{2n \choose 2i} - \sum_{i = 0}^{n - 1}{2n \choose 2i + 1} \right) \frac{(-1)^{n - 1}}{(2n)!} x^{2n} \\ & = 1 + \sum_{n = 1}^\infty \left(\sum_{j = 0}^{2n}(-1)^j{2n \choose j} \right) \frac{(-1)^{n - 1}}{(2n)!} x^{2n} \\ & = 1 + \sum_{n = 1}^\infty \left(1-1\right)^{2n} \frac{(-1)^{n - 1}}{(2n)!} x^{2n} = 1\,. \end{align} $$

$\endgroup$
1
  • 1
    $\begingroup$ I fixed a typo for you 😄 $\endgroup$ Apr 3, 2020 at 18:24
2
$\begingroup$

There is an easy solution using complex numbers (but not the complex exponential): $$ \begin{align} \sin^2 x + \cos^2 x & = \left(\cos x + i \sin x\right)\left(\cos x - i \sin x\right) \\ &=\left(\sum_{j=0}^{\infty} (-1)^j \frac{x^{2j}}{(2j)!} + i \sum_{j=0}^{\infty} (-1)^j \frac{x^{2j+1}}{(2j+1)!}\right)\left(\sum_{j=0}^{\infty} (-1)^j \frac{x^{2j}}{(2j)!} - i \sum_{j=0}^{\infty} (-1)^j \frac{x^{2j+1}}{(2j+1)!}\right)\\ &=\left(\sum_{k=0}^{\infty} i^k \frac{x^{k}}{k!}\right) \cdot \left(\sum_{k=0}^{\infty} (-i)^k \frac{x^{k}}{k!}\right). \\ \end{align} $$ (Of course these last two factors are equal to $e^{ix}$ and $e^{-ix}$, but we do not need this fact: we are just manipulating power series here.) We need to show that the above product is $1$, so that the coefficient of $x^\ell$ in the above product is $1$ if $\ell=0$ and $0$ otherwise.

Expanding the product, we get that the coefficient of $x^\ell$ equals $$ \sum_{k_1+k_2=\ell} \frac{i^{k_1}}{k_1!} \cdot \frac{(-i)^{k_2}}{k_2!}=\sum_{k_1+k_2=\ell} (-1)^{k_2} \frac{i^{\ell}}{k_1!k_2!} = \sum_{k_1=0}^\ell (-1)^{\ell-k_1}\frac{i^{\ell}}{\ell!} \binom{\ell}{k_1}. $$ In view of the well-known binomial coefficient identity $\sum_{k=0}^{\ell} (-1)^k \binom{\ell}{k}=0$ for any integer $\ell>0$, which may be obtained by expanding the identity $(1-1)^{\ell}=0$, the above sum vanishes when $\ell>0$, and when $\ell=0$ it equals $1$, as can be computed directly. Which is precisely what we had to show.

$\endgroup$
1
$\begingroup$

Define $f: \mathbb{R} \rightarrow \mathbb{R}$ by $$ f(x) = \text{sin}^2(x) + \text{cos}^2(x). $$ From the chain rule it follows that $$ f'(x) = 2\cdot \text{sin}(x) \cdot \text{sin'}(x) + 2\cdot \text{cos}(x) \cdot \text{cos'}(x) = 2\cdot \text{sin}(x) \cdot \text{cos}(x) + 2\cdot \text{cos}(x) \cdot (-\text{sin}(x)) = 0, $$ as we know that $\text{sin'}(x) = \text{cos}(x)$ and $\text{cos'}(x) = -\text{sin}(x)$. We will now show that if the derivative equals zero, the function is constant, using the Mean-value theorem. Let $a,b\in \mathbb{R}$, with $a<b$. As $f$ is differentiable, and hence also continuous, on $\mathbb{R}$, we know there exists a $c\in (a,b)$ satisfying $$ f'(c) = \frac{f(b)-f(a)}{b-a}. $$ As we know that $f'(c) = 0$ for all $c \in \mathbb{R}$, multiplying both sides of the equation by $b-a$ yields $f(b)-f(a)=0$. Equivalently, $f(b) = f(a)$ for all $a,b\in \mathbb{R}$, where $a<b$. Hence $f$ is constant on $(a,b)$. Note that $$f(0)= \text{sin}^2(0) + \text{cos}^2(0) = ( \sum_{k=0}^\infty (-1)^k \cdot \frac{1}{(2k+1)!} 0^{2k+1} )^2 + ( \sum_{k=0}^\infty (-1)^k \cdot \frac{1}{(2k)!} 0^{2k} )^2 = 0 + 1 = 1, $$ as only the first term of the cosine power series yields a nonzero value, namely 1 ($(-1)^0 \cdot \frac{1}{(0)!}0^0=1$, since $(-1)^0=1$, $0!=1$ and $0^0=1$).

In conclusion, for all $x \in \mathbb{R}$, $f(x)=1$, so that $$ \sin ^{2}(x)+\cos ^{2}(x)=1. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.